The power of data driven decision-making; using information, insight and action to make a positive impact on students and enact change in the classroom. - Adams, Stacey (2017)
This small-scale piece of research aimed to investigate the power of data driven decision making to see how information, insight and action could be used to make a positive impact on students. Data is often underutilised by teachers and managers alike as it can be seen as impenetrable, overwhelming and/or irrelevant. The research aimed to look at how capacity building interventions could be introduced for both teachers and managers. Questionnaires and interviews were used with teachers, managers, leaders and senior leaders to uncover how to redesign our approaches to data to have a more positive impact on students. Sociocultural learning theory, capacity building interventions, sense making theory and cognitive biases formed a central consideration in the production of a number of recommendations for educational leaders such as streamlining and reducing the amount of data, providing a social environment for learning and overtly raising awareness of cognitive biases. Furthermore, an artefact was developed to be used as a capacity building intervention for both teachers and managers alike. The research concluded that joining the two areas of data based decision-making and cognitive biases could be a promising capacity building intervention for both teachers and managers.